"The land of football": An analysis of media coverage of the 2014 FIFA World Cup and its effects on people's perceptions of Brazil. (September 2019) - Schallhorn, Christiana
Abstract: Mega-sporting events are followed by a global audience. Through numerous telecasts and productions shown during pre- and post-match coverage or in news media reports, the audience is provided with many insights and substantial background information about the host country. This visibility in the international media offers host countries a good opportunity to promote themselves. This study explores whether the media coverage during the 2014 FIFA World Cup in Brazil influenced Germans' perceptions about the host country. A content analysis of topic-related articles ( N = 3, 419) from German telecasts, newspapers, and online media was performed to identify the main topics and tone in media coverage (study 1). Additionally, a two-wave panel survey was conducted before and after the World Cup, asking participants ( N = 431) about their attitudes toward Brazil-related topics (study 2). Results indicate that coverage was mostly homogenous across all of the media channels with regard to the frequency and tone of the addressed topics. Findings from the panel survey show that especially those topics and media messages that were most frequently reported (e.g., nature and safety) or that were predominantly negative (e.g., the standard of living and economic situation) influenced people's perceptions of Brazil in line with the coverage. It is concluded that transferred information about host countries has the power to influence the way in which these countries are perceived by the media audience. The role of the media in the process of image building and its implications for host countries are discussed.